Inferior endothelial function improved following optimisation of asthma control in children. (November 2022) - Chan, Kate C.; Au, Chun T.; Wong, Emily; Chook, Ping; Li, Albert M.
Abstract: Association between asthma control and cardiovascular disease (CVD) remains highly plausible as the two are related to chronic systemic inflammation. Children with physician-diagnosed asthma and matched healthy controls underwent endothelial function assessment. Repeat measurements were performed in uncontrolled asthmatics after initiation or up-titration of inhaled corticosteroids (ICS), compared to those with well-controlled asthma without ICS therapy. We found that children with uncontrolled asthma had inferior endothelial function compared to matched healthy controls. Enhancement in endothelial function, lung function and symptom control was observed in uncontrolled asthmatics after initiation or up-titration of inhaled corticosteroids (ICS). These results provided further evidence of a likely relationship between asthma control and cardiovascular health. Highlights: Asthma and cardiovascular disease share a common pathway, mediated by chronic systemic inflammation. Children with uncontrolled asthma have inferior endothelial function compared to matched healthy controls. Optimization of asthma control leads to better lung function, reduced airway inflammation and improved endothelial function.